Legal Aspects In Handling Money Laundering Cases In Indonesia - Riswanto, Riswanto; Akbar Rachmatullah, Muhammad; Rahman, Alip; Dikrurahman, Diky (Asian Journal of Social and Humanities, 2024)
Money laundering poses a serious threat to the integrity of the financial system and the stability of society, prompting the need for effective handling from all parties involved. This research discusses the legal aspects of handling money laundering cases in Indonesia. Using a descriptive-analytical qualitative approach, this study analyses the existing legal framework, its implementation in law enforcement practice, and the challenges faced by law enforcement officials in handling money laundering cases. Data was collected through literature study and analysis of money laundering cases that have been decided by the court. The results show that although Law No. 8/2010 has provided a strong legal foundation, there are still challenges in its implementation including limited resources, inter-agency coordination, and the development of increasingly sophisticated money laundering methods. Based on these findings, this research presents policy recommendations to strengthen law enforcement in handling money laundering offences in Indonesia.